Parâmetros reprodutivos e condição corporal de três espécies do gênero Astyanax em riachos interceptados por diferentes formas de tubulações - Celestino, Elaine Fernandes (2011)
The increase in road construction associated with urbanization can result in habitat fragmentation and loss of fish populations in streams. In this study, we document aspects of reproductive biology and the degree of animal welfare in three species of the genus Astyanax, through analysis of the upstream and downstream sections (above and below) in two distinct forms of culvert (square and circular) in two streams second order tributaries of the Paraná River. For attributes such as reproductive gonadosomatic ratio, diameter of oocytes and fertility did not differ between the sections of the culvert studied. However, the standard length, sex ratio, gonad maturation stages and the condition factor showed significant differences for the species. Be deduced that the species A. altiparanae presents best adapted to the harsh conditions of the culvert and can possibly accomplish movements upstream and downstream of the different types of culvert. While for A. paranae and A. fasciatus results suggest that these species are affected by the culvert e may restrict or hinder movement.